Intermolecular interactions, spectroscopic and theoretical investigation of 4-aminoacetophenone - Rocha, Mariana; Di Santo, Alejandro; Ben Altabef, Aida; M. Gil, Diego (International Journal of Advanced Chemistry, 2019)
The molecular structure of 4-aminoacetophenone (PAAP) was determined by DFT calculations using different basis sets. The structural parameters, electronic properties and vibrational wavenumbrers of the optimized geometry have been determined. The vibrational wave-numbers of the fundamental modes of the title compound have been precisely assigned and analyzed and the theoretical results are compared with the experimental vibrations observing a very good correlation. TD-DFT approach was applied to assign the electronic transitions ob-served in the experimental UV-vis spectrum. The molecular electrostatic potential map was used to identify the possible electrophilic and nucleophilic sites. Natural bond orbital (NBO) analysis and atoms in molecules (AIM) approach are applied in order to quantify the relative strength of hydrogen bonding interactions and to account their effect on the stabilities of molecular arrangements. In addition, a detailed exploration of the intermolecular interactions that stabilizes the crystal packing has been performed by using the Hirshfeld surface analysis.Â Â Â